Digitising Interpretation: Transforming Tafsir Al-Mishbah in the Context of the Living Quran - Isnaini, Subi Nur; Ali, Rijal (UIN Sunan Kalijaga Yogyakarta, 2024)
This research aims to explore the relationship between digitizing interpretation, texts, messages, and societal practices through the transformation, reception, and deconstruction of Tafsir Al-Mishbah. The issue of digitizing interpretation is often viewed solely through the lens of technological transition and historical narrative, overlooking its societal implications. This study seeks to delve into the interplay among these elements by examining the digitization process, features of the digital application, and societal reception of Tafsir Al-Mishbah. It outlines three problem formulations: the digitalization process, features in the digital application, and reception within the digitization phenomenon. To address these formulations, a qualitative netnographic research method was employed. Data were collected through observation and documentation, primarily from video recordings on the Quraish Shihab YouTube channel, which provides insights into the digitization process and various versions of Tafsir Al-Mishbah. The research concludes that digitalization serves as a means to transform Tafsir Al-Mishbah, enabling independent Qur’an study while maintaining ties with authoritative figures. It bridges innovations with limitations present in printed editions, catering to the public's needs. Furthermore, the digitization of Tafsir Al-Mishbah is closely tied to Quraish Shihab's interpretation of divine promises, as referenced in QS. al-Qamar [54]: 17, 22, 32, and 40. This study highlights the often-overlooked aspects of digitalization, showcasing its relationship with innovation, ideology, and public reception. It underscores that the transformation of religious texts, including the Qur’an and Tafsir, contributes to the discourse on the living Qur’an and living Tafsir.